2020
DOI: 10.1109/access.2020.2974496
|View full text |Cite
|
Sign up to set email alerts
|

DIC: Deep Image Clustering for Unsupervised Image Segmentation

Abstract: Unsupervised segmentation is an essential pre-processing technique in many computer vision tasks. However, current unsupervised segmentation techniques are sensitive to the parameters such as the segmentation numbers or of high training and inference complexity. Encouraged by neural networks' flexibility and their ability for modelling intricate patterns, an unsupervised segmentation framework based on a novel deep image clustering (DIC) model is proposed. The DIC consists of a feature transformation subnetwor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…For clinical tasks for which it is difficult to obtain manually‐annotated ground truth data, unsupervised CNNs have been applied to solve the segmentation problem. Zhou et al proposed a deep image clustering model to assign pixels to different clusters by updating cluster associations and cluster centers iteratively 185 . CNN could also be used to generate radiomic signatures for various clinical applications based on tumor subregions and be used in OS prediction, treatment response prediction, and clinical risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…For clinical tasks for which it is difficult to obtain manually‐annotated ground truth data, unsupervised CNNs have been applied to solve the segmentation problem. Zhou et al proposed a deep image clustering model to assign pixels to different clusters by updating cluster associations and cluster centers iteratively 185 . CNN could also be used to generate radiomic signatures for various clinical applications based on tumor subregions and be used in OS prediction, treatment response prediction, and clinical risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al [14] proposed a real-time segmentation system called Hierarchical Feature Selection (HFS) that first uses over-segmentation to acquire seed regions. Zhou and Wei [15] proposed a deep image clustering (DIC) model, which consists of a feature transformation subnetwork (FTS) and a differentiable deep clustering subnetwork (DCS) for dividing the image space into different clusters. Ilyas et al [16] proposed a CNN-based architecture for unsupervised segmentation that combined CNN architecture with a graphbased method to generate the target segments.…”
Section: A Unsupervised Segmentationmentioning
confidence: 99%
“…These methods include PEF+K-means [29], MCG [30], gPbowt-ucm [2], LGM [31], and HFS method [14]. In addition, we evaluate the proposed method with two unsupervised segmentation methods based on convolution networks: W-Net [32] and DIC [15].…”
Section: E Comparison Experimentsmentioning
confidence: 99%
“…[51] A large quantity of research studies have recently applied the correlation clustering framework to image segmentation, and there was a lot of effort to extract better region-based features between neighboring superpixels [52], [53], [54], [55]. Zhou and Wei [56] proposed an unsupervised segmentation framework based on a novel deep image clustering (DIC) model and the results showed that DIC is less affected by the segmentation parameter, such as cluster numbers, and of lower computation cost. The Kmeans algorithm (or Lloyd's algorithm) is the most commonly used technique in the clustering-based segmentation field.…”
Section: Related Workmentioning
confidence: 99%